2021
DOI: 10.4102/ajopa.v3i0.41
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the English version of the Stress Overload Scale in a sample of employed South Africans

Abstract: Amidst reports of high levels of stress in South Africa, it remained difficult to quantify psychological stress in the absence of locally validated measures. This study explored the English version of the Stress Overload Scale (SOS) in a South African sample. The first aim was to replicate the basic psychometric analysis of the original English version used in American samples, as well as the Setswana version used in a South African rural community setting. The second aim was to investigate criterion validity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Fourthly, current stress overload was measured with the 10-item Stress Overload Scale – Short Form (SOS-S) ( Amirkhan, 2018 ; Wilson et al, 2018 ; Van Wijk, 2021 ), to indicate instances where a participant’s demands were experienced as overwhelming their available resources (α = 0.90 for this study). Previous SA research suggested that a score of >20 was associated with significant mental health difficulties ( Van Wijk, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Fourthly, current stress overload was measured with the 10-item Stress Overload Scale – Short Form (SOS-S) ( Amirkhan, 2018 ; Wilson et al, 2018 ; Van Wijk, 2021 ), to indicate instances where a participant’s demands were experienced as overwhelming their available resources (α = 0.90 for this study). Previous SA research suggested that a score of >20 was associated with significant mental health difficulties ( Van Wijk, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous SA research suggested that scores > 20 were associated with significant mental health difficulties (Van Wijk, 2021).…”
Section: Indicators Of Common Mental Disordersmentioning
confidence: 98%